Cancer gene therapy a challenge for the XXI century - Mackiewicz, Andrzej; Nawrocki, Sergiusz (Contemporary Oncology/Współczesna Onkologia, 2000)
Genes used in human cancer gene therapy may be classified into four groups: genes restoring control of the cell cycle and apoptosis (i.e. p53), suicide genes, sensitising the cell for toxic metabolites (i.e. HSVtk (HSV thymidine kinase), genes promoting elimination of cancer cells by immune system (such as: genes encoding tumour antigens, HLA proteins, co-stimulatory molecules (B-7.1) and cytokines), genes interfering with tumour angiogenesis. As well as testing of therapeutic genes in animals’ models and in clinical trials, gene therapy develops tools for genes’ delivery because only elimination of every clonogenic cancer cell assures the full control of cancer. So far retroviral vectors were used in most of clinical trials. Nowadays, adenoviral II-generation vectors, retroviral-C vectors, lentiviral and hybrid vectors are introduced. Targeting gene expression to a specific tissue or cell population is also possible. Since currently used tools for gene transfer are not able to deliver the therapeutic gene to every tumour cell, bystander effect is explored and enhanced. In the Department of Cancer Immunology in Poznań since 1996 we have vaccinated 170 patients with advanced melanoma with cellular vaccine genetically modified with IL-6 and sIL-sR genes using double copy dicistronic retroviral vector. We have observed clinical responses in about 20% of patients and stable disease in 30% of patients. Now we are preparing a new generation of adenoviral vectors, which will be used for intratumoural gene therapy of melanoma and renal cell carcinoma patients.